Better Approximation Properties by New Modified Baskakov Operators - Ahmed F. Jabbar; Amal K. Hassan (Journal of Applied Mathematics)
This paper introduces a new idea to obtain a better order of approximation for the Baskakov operator. We conclude two new operators from orders one and two of the Baskakov type. Also, we prove some directed results concerning the rate of convergence of these operators. We apply the Maple software to demonstrate how the operators converge to a specific function.